California Dreams and Nightmares - Michaličková, Alexandra (American & British Studies Annual, 2015)
Ever since the discovery of gold in 1848, people have been coming to California in belief that they would be rewarded generously for their hard work and talents. California was thus perceived as the promised land of opportunity and fulfilled dreams. However, for many the dream did not come true. The paper analyses California’s most prominent groups of immigrants arriving to California during the Gold Rush and afterwards paying attention to their initial expectations and reasons for coming and contrasts them with conditions they encountered.